Kajian Kostum Solo Batik Carnival 2019 dengan Pendekatan Antropologi Seni - Nurul Fajar Setiyono; Setyawan Setyawan (Ornamen, 2022)
This research aims to find out how Solo Batik Carnival performance viewed from an anthropological perspective. Therefore, it can be a reflection for the parties involved in the art performance in terms of the design contained in the batik clothing, the materials used, and describe the performance used in batik clothing. This research was conducted in Surakarta City, especially in the preparation, implementation, and post-implementation of Batik Solo Carnival (SBC) in 2019. The data source is primary data. It is from randomly selected informants in concarnival activities and secondary from supporting documents and journals. The methods of data collection is using method of observation, In Depth Interview, and documentation. The data analysis technique used in this study is interactive data analysis with a qualitative approach from theory of art anthropology. adventure Timor Leste, Vietnam Timeless Charm, Kingdom of Wonder Cambodia, Wonderfull Indonesia, Uniquely Singapore, Malaysia Truly Asia, Kay Ganda Philippines, Simply Beautiful Laos, and The Green Heart of Brunei. It is based on various types of costumes displayed from various countries, and then analyzed based on the design, batik materials and performance in appearance. impression of splendor, luxury, glamor, and festivity. (2) Batik material is a heritage has undergone extraordinary sophistication. It is especially for Javanese batik has the richest decorative patterns, the most developed coloring techniques, and the most perfect manufacturing techniques compared to batik from other regions (3) The performance of the 2019 Solo Batik Carnival is not only as a festive carnival event but also as a tool in introducing the culture of each ASEAN country.